Study on mechanical, hydrophobic and corrosion resistant properties of methylsiloxan-based mortar modified by micro-nano supplementary cementitious materials - Kangjie Zhang; Weizhun Jin; Yajun Lv; Shuguang Li; Xianlei Zhang; Tengfei Xiang; Changkuan Gu; Weifeng Bai; Caihong Song; Jun Zhao (Journal of Materials Research and Technology)
Concrete with porous hydrophilic properties is easily attacked by corrosive ions, which seriously affects the durability of concrete structures. The incorporation of hydrophobic powder is beneficial to the durability of cementitious materials, but will reduce the mechanical properties. Based on this, the effects of silica fume (SF), nano silica (NS), and nano calcium carbonate (NC) on the improvement of mechanical properties, hydrophobic, and corrosion resistance of methylsiloxan-based hydrophobic powder (MSHP) modified mortar were studied, and the hydration products, micromorphology, and pore structure of mortar were also characterized. The results show that the addition of MSHP can prolong the setting time of mortar, while micro-nano supplementary cementitious materials can shorten the setting time. The addition of NS helps to increase the compressive strength of mortar, and the compressive strength at 28 d increases by 9.4%, up to 60.4 MPa. Meanwhile, the addition of NC and SF helps to increase the compressive strength at early stage, but not conducive to the improvement of compressive strength at later stage. When 4% MSHP is added, the mortar mixed without supplementary cementitious materials and with SF and NS have superhydrophobic performance, and the water contact angle reaches 150.7°, 151.7°, and 152.4°, respectively, while the mortar mixed with NC cannot obtain the superhydrophobic performance and the water contact angle is only 139.7°. MSHP can significantly improve the corrosion resistance of mortar and the addition of SF and NS can further enhance this performance, while the addition of NC is not conducive to the improvement of corrosion resistance.